Does it make a difference? Examining consumers´ attitude towards sustainability efforts within the fast fashion industry through trust and perceived consumer effectiveness - Neumann, Hannah Laura (2018)
In the context of environmental sustainability in the fashion industry, developing positive consumer perceptions and attitudes about efforts of companies to take responsibility, as well as trust is vital in terms purchase intention. Furthermore, perceived consumer effectiveness, a feeling of empowerment in consumers to contribute to solving environmental problems, is found to be a strong predictor of environmentally conscious consumer behavior. It remains yet unanswered, if these concepts apply to the setting of two well-known fashion brands, ZARA and H&M, and their sustainable clothing lines, and if favorable perceptions about these brands could enhance perceived consumer effectiveness. To answer these questions, we developed a framework that depicts the relationships between perceptions of social responsibility, consumer attitude, trust, purchase intention, and perceived consumer effectiveness. An online survey was conducted with an internationally diverse sample of 216 consumers, and the data was analyzed using partial least squares structural equation modeling. The results indicated that perceptions of social responsibility directly affect consumers’ attitudes towards ZARA and H&M, as well as trust and perceived consumer effectiveness. Trust was found to be a direct predictor of purchase intention. Consumer attitude and perceived consumer effectiveness, however, did not predict purchase intention. Results are discussed, and theoretical and practical implications are presented.